A STUDY ON FIBERGLASS CONSTRUCTION AS LAMINATION FOR BOAT ACCORDING TO STANDARD RULES (Jurnal Sains & Teknologi Fakultas Teknik Universitas Darma Persada, 2022)
Indonesia as a maritime country has a dependency on marine vessels for the transport and conveyance economic functioning. In this regard Boat used for many years made of wood, but because of the nature of the weathered wood that easily weather and chemical factors and requires an adequate treatment with the course of time it came in the form of laminated fiberglass FRP (Fiber Reinforced Plastics) as a substitute timber in which the material is mepunyai many advantages not possessed by the wood so that the ship was made of FRP from a place in the world shipbuilding in particular the producers of the ship. However, in a survey conducted at several shipyards in 2009 showed that the design, construction and fiberglass hull lamination process generally do not have clear standards that would pose a significant risk of an accident. To minimize these conditions, the production vessel is based on the FRP laminate should refer to existing standards that BKI rules that involves strict requirements such as tensile testing, bend testing, and so forth. Keywords: ship production, FRP lamination, tensile test, bending test